Bottom-up synthesis of nitrogen-containing graphene nanoribbons from the tetrabenzopentacene molecular motif. (December 2020) - Feng, Zhijing; Mazaheripour, Amir; Dibble, David J.; Wagner, Peter; Czap, Gregory; Kladnik, Gregor; Cossaro, Albano; Verdini, Alberto; Floreano, Luca; Bavdek, Gregor; Ho, Wilson; Comelli, Giovanni; et al.
Abstract: Atomically-defined graphene nanoribbons (GNRs), which are narrow strips of graphene that feature a quantum confinement-induced bandgap, have shown great promise for applications in the next generation of semiconductor devices. Although numerous studies have demonstrated the bottom-up synthesis of all-carbon GNRs, a comparatively limited number of reports have focused on the preparation of nitrogen-doped GNRs, with two general types of architectures demonstrated to date. Herein, we describe the design, synthesis, and characterization of a new class of nitrogen-containing GNRs consisting of repeating tetrabenzopentacene molecular subunits. Our findings may afford additional possibilities and opportunities with regard to the directed bottom-up synthesis of heteroatom-doped, carbon-based nanoscale electronics. Graphical abstract: Image 1